ANALISIS STRATEGI KOMUNIKASI PEMASARAN MERCHANDISE DI KEDAI DIGITAL 8 SOLO (Studi Kasus Strategi Komunikasi Pemasaran) - Mardiyanto, Doni; Slamet, Giarti (Universitas Of Surakarta, 2019)
This title of this research is ANALYSIS OF MARKETING COMMUNICATION STRATEGY (Case Study of Marketing Communication Strategy Merchandise at Kedai Digital 8 Solo). This research examines marketing communication strategy in increasing merchandise product sales at Kedai Digital 8 Solo. This research uses descriptive qualitative method, qualitative descriptive method is research that describe the object under study based on facts that exist in the field. Data are presented using primary data and secondary data through structured interview, observation, and documentation, then analyzed with qualitative data analysis. Based on the analysis of this research, results show: (a) Kedai Digital 8 Solo apply advertising and direct marketing as marketing communication strategies, (b) The advertising using media Brochures, banners / MMTs and social media, (c) The direct marketing using letter / proposal submitted to individuals and companies/agencies, (d) Advertising via social media (online) is done on a regular basis as it is more effective and efficient than direct advertising, (e) Direct marketing through letter/proposal medium is done Periodically at least once a year or even rarely